Service Supply Chain Management in the Performance of National Logistics Agency in National Food Security - Maun Jamaludin; Teddy Hikmat Fauzi; Deden Novan Setiawan Nugraha; Latifah Adnani (International Journal of Supply Chain Management, 2020)
The main food problems in the context of realizing strong food security include increasingly scarce availability, increasingly difficult food affordability, both physically and economically. Food security are increasingly worrying because of the increasing number of problems related to food safety. From this problem, there is a tendency for the food situation, especially in international markets, which is increasingly unpredictable and increasingly unstable. For this reason, to achieve resilient and sustainable food security, government policies in the food and agriculture sector are more comprehensive, and are able to respond directly to challenges in the food sector. The policy must be able to adopt and encourage the effective and efficient use of food from all natural resources available in this country in an effective, efficient and sustainable manner. The research methodology used in this study is to use a qualitative descriptive approach at logistics bureau (Bulog) in strengthening food security strategies in West Java by using service supply chain management assessment. In terms of its service, the results show that the performance of the of the West Java Logistics Bureau () in achieving food security. From the indicators of responsibility, it was conducted in accordance with applicable regulations and policies and in accordance with standard operating procedures that apply in providing services and conducting operational activities. From the responsive indicator, the agency in establishing food security has involved the community in the procurement or absorption of staple food as the working partner. From the indicators of effectiveness, the performance has increased and reaches the target to improve the quality of performance in each target area with good results.